A comparative study of the MARA appliance and the Activator-Headgear combination in the treatment of Class II Division 1 malocclusion - Brito, Deborah Brindeiro de Araújo (2017)
The treatment of Class II Division 1 malocclusion using orthopedic devices combined with fixed orthodontic appliances has shown excellent results when used in growing patients. This study aimed to compare the treatment effects of Class II correction with MARA appliance (G1), AcHg combination appliance (G2), and an untreated control group (G3). Each experimental group was composed of 18 patients, with a baseline mean age of 11.70 (G1) and 10.88 (G2) years, treated for a mean time of 3.60 (G1) and 3.17 (G2) years. The control group (G3) consisted of 20 individuals with a baseline mean age of 11.07 years. The groups were evaluated before (T1) and after (T2) treatment. Lateral cephalometric radiographs were used to evaluate skeletal and dentoalveolar changes upon treatment (T2-T1), and a comparable period was used for the control group. Intergroup comparisons regarding treatment changes were performed using repeated measures analysis of variance (ANOVA) followed by Tukeys test. The dentoalveolar effects and maxillary restriction improved the maxillomandibular relationship in G1 and G2. Mandibular alterations were mainly due to natural craniofacial growth, with no significant alterations of soft tissues. It was concluded that both the appliances corrected similarly the Class II malocclusion.